80-MHz bandpass ΔΣ modulators for multimode digital IF receivers. - Salo, T.O (IEEE Journal of solid state circuits)
Three fully differential bandpass (BP) ΔΣ modulators are presented. Two double-delay resonators are implemented using only one operational amplifier. The prototype circuits operate at a sampling frequency of 80 MHz. The BP ΔΣ modulators can be used in an intermediate-frequency (IF) receiver to combine frequency downconversion with analog-to-digital conversion by directly sampling an input signal from an IF of 60 MHz to a digital IF of 20 MHz. The measured peak signal-to-noise-plus-distortion ratios are 78 dB for 270 kHz (GSM), 75 dB for 1.25 MHz (IS-95), 69 dB for 1.762 MHz (DECT), and 48 dB for 3.84 MHz (WCDMA/CDMA2000) bandwidths. The circuits are implemented with a 0.35-μm CMOS technology and consume 24-38 mW from a 3.0-V supply, depending on the architecture.